Pengaruh Penguatan Positif Terhadap Self Awareness - Rahmawati; Octiarini, Dinda Fitri; Handoyo, Alfiandy Warih (SISTEMA: Jurnal Pendidikan, 2021)
ABSTRACT The purpose of the study was to determine the level of self- awareness and the effect of positive reinforcement techniques in increasing and raising self-awareness in students. This research was conducted at SMA Negeri 6 Tangerang Regency. The type of research used in this research is pre-experimental using a single subject or called SSR (Single Subject Research), with a population of 113 students in class XI IPA and a sample of 5 people selected by purposive sampling technique. Methods of collecting data using self-awareness questionnaires, interviews and observation. The results of the analysis of research data that have been described by researchers, it can be seen that positive reinforcement techniques have a positive influence on the ability to increase and raise self-awareness. This is indicated by the data of the five research subjects which showed that the percentage results in the intervention phase and baseline-2 (A2) were higher than thephase baseline-1 (A1). Subjects 1 to 5 in thephase baseline-1 (A1) obtained results of 33% which is a natural condition without any treatment or intervention on the subject. Furthermore, there was an increasing change in the intervention phase (B) with an average of 83.12%, 81.87%, 81.75%, 77.50%, 77.37%. The data were obtained because the subject had been given treatment or intervention. by applying the positive reinforcement technique in thephase baseline-2 (A2) obtained 78%. These results are based on the results of the five subjects before, during and after being given the service. The achievement of these data indicates a positive influence on the ability to increase and raise self-awareness. Keywords: positive reinforcement technique, self awareness